Design Thinking Problems in Determining Solution for Creative Gift Orders - M. Azman Maricar; Dian Pramana; Edwar Edwar (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
Selda Design has a business selling custom merchandise or creative gifts that use social media and Whatsapp to serve customers. During its implementation, it was tiring because you have to repeatedly send detailed product information to each customer. The owner wants to develop his digital-based business. Therefore it is necessary to research to find out how the response of the admin team who handles orders from customers, and customers as product orders to the solutions provided. The design thinking method is used to provide solutions that can overcome the problems at hand. Design thinking has two processes, namely, problem space and solution space. This research focuses on problem space design thinking which includes the stages of empathy, defines, and ideate. From these stages, a solution is generated in the form of a wireframe. To determine whether the given wireframe can solve the problem, the wireframe is made in two variations. These were tested directly to the user with the A/B Testing method. The results of the wireframe test for the owner and admin team are 100% choosing version A, because of efficiency, data management, and menu selection. Wireframe intended for customers has obtained results, 77.78% chose version A, and 22.22% chose version B. Version A was chosen because of its efficiency, ease of use, and ease of access to the menu provided. Based on these results, it was determined that the wireframe version A for each user would be used as the next stage of product development. From these results, problem space design thinking can answer the problems faced by providing solutions for users.